Elder‐Clowning in Long‐Term Dementia Care: Results of a Pilot Study. Issue 2 (February 2016) - Kontos, Pia; Miller, Karen‐Lee; Colobong, Romeo; Palma Lazgare, Luis I.; Binns, Malcolm; Low, Lee‐Fay; Surr, Claire; Naglie, Gary
Abstract : Objectives: To assess the effects of elder‐clowning on moderate to severe behavioral and psychological symptoms of dementia (BPSD) in nursing home residents with dementia, primarily of the Alzheimer's type. Design: Before‐and‐after study. Setting: Nursing home. Participants: Nursing home residents with moderate to severe BPSD, as defined according to a Neuropsychiatric Inventory—Nursing Home version (NPI‐NH) score of 10 or greater (N = 23), and their care aides. Intervention: A pair of elder‐clowns visited all residents twice weekly ( 10 minutes per visit) for 12 weeks. They used improvisation, humor, empathy, and expressive modalities such as song, musical instruments, and dance to individualize resident engagement. Measurements: Primary outcomes were BPSD measured using the the NPI‐NH, quality of life measured using Dementia Care Mapping (DCM), and nursing burden of care measured using the Modified Nursing Care Assessment Scale (M‐NCAS). Secondary outcomes were occupational disruptiveness measured using the NPI‐NH, agitation measured using the Cohen Mansfield Agitation Inventory (CMAI), and psychiatric medication use. Results: Over 12 weeks, NPI‐NH scores declined significantly ( t 22 = −2.68, P = .01), and DCM quality‐of‐life scores improved significantly ( F 1, 50 = 23.09, P < .001). CMAI agitation scores decreased nominally, but the difference was not statistically significant ( t 22 = −1.86, P = .07). Occupational disruptiveness score significantly improved ( t 22 = −2.58, P = .02), but there was no appreciable change in M‐NCAS scores of staff burden of care. Conclusion: Results suggest that elder‐clowning reduced moderate to severe BPSD of nursing home residents with dementia, primarily of the Alzheimer's type. Elder‐clowning is a promising intervention that may improve Alzheimer's disease care for nursing home residents.